Comparison study of disaggregated ODA and FDI impact on welfare of ODA recipient coutries - LEE, Youngji (KDI School, 2015)
This study compares effect of ODA, Disaggregated ODA and FDI on developing countries’ welfare. The aim of this paper is to seek the most efficient way of promoting inclusive growth and help development entities to forge development strategy. Econometrics estimation, using panel data of 108 ODA recipient countries from period of 2005 to 2013, suggests that FDI has higher impact than ODA on HDI when observed with overall samples, but mixed results were drawn based on different regions and income levels. The major findings of this empirical study are; first, ODA as a whole does not have significant impact on HDI, but marginal impact of disaggregated ODA on welfare is positive, second, when tested by disaggregated ODA, economic infrastructure ODA has higher impact than FDI, third, policy interaction terms of disaggregated ODA have a positive impact on HDI in Lower Middle Income Countries. This implies that aid practitioners should be cautious when setting a strategy, and take an individual approach based on partner countries’ context.
Thesis(Master) --KDI School:Master of Development Policy,2015